Sistem Informasi Pengelolaan Data Alumni Pada UPT SMK Negeri 1 Musi Banyuasin - Risviliani Afrilia; Zaid Romegar Mair; Juansyah Juansyah (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2021)
This research was conducted to create an Alumni data management information system at UPT SMK Negeri 1 Musi Banyuasin. This system designed specifically for managing alumni data is expected to make it easier for staff to manage alumni data and make it easier for alumni to fill in alumni data without having to come to school. The focus in this research is to create a system using programming languages ​​that have been widely used, namely PHP and MySQL and to report the data using FPDF. Data Collection Methods in this study are about the Alumni data management information system at UPT SMK Negeri 1 Musi Banyuasin. This study shows the results that to present information on the Alumni of UPT SMK Negeri 1 Musi Banyuasin which includes the presentation of alumni data. As well as other information that is deemed necessary to be presented when needed, such as facilitating the search for old or new alumni. The development of this web-based information system will make it easier to handle changes in data, be it adding, subtracting or searching for data.